Strategi Komunikasi dalam Peralihan Layanan Digital PT Bank Negara Indonesia - Octaviani, Siti Aisyah (Jurnal Dinamika Ilmu Komunikasi, 2025)
This study aims to analyze the communication strategies implemented by BNI KC Pasar Mayestik in managing the transition toward digital services and to explore customer feedback regarding the transformation process. A qualitative descriptive method was employed, involving in-depth interviews, field observations, and documentation of digital service activities. The findings reveal that BNI KC Pasar Mayestik adopted adaptive, empathetic, and participatory communication strategies to enhance customer understanding of the service changes. These strategies were carried out through the development of clear messages, the balanced use of digital and face-to-face communication channels, and intensive staff training to improve digital communication competence. Empathetic communication emerged as a key factor in maintaining customer trust during the transition period. Customer feedback indicated that most clients felt supported and guided in adapting to the new digital systems. This research contributes to the development of the E-Leadership Communication Adaption Model (ECAM) by emphasizing the significance of human-centered and responsive strategic communication in ensuring the success of digital transformation within the banking sector.